THE TECH STOCKS' PARADOX: UNRAVELING THE UNEXPECTED DECLINE AMID INDONESIA'S DIGITAL ECONOMY BOOM - Syahputra, Andry; Gunawan, Didik; Cahyadi, Lukieto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of digital economy growth, macroeconomic factors, and stock liquidity on the stock prices of Indonesia’s technology sector during the period of January 2021 to December 2024. Employing a quantitative approach, this research utilizes the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method processed through the SmartPLS software. The study relies on secondary monthly data, including digital indicators such as private funding value and internet user growth, macroeconomic indicators such as interest rates and exchange rates, and liquidity indicators such as trading volume and frequency. The results indicate that digital economy growth has a positive and significant effect on technology sector stock prices, while macroeconomic factors show a negative and significant impact. Meanwhile, stock liquidity does not exhibit a significant effect. These findings offer new insights into the dynamics of technology stocks in Indonesia, which do not always align with digital development, and highlight the critical role of macroeconomic conditions in investment decision-making. This research is expected to contribute to the development of digital financial strategies in the national context. Keywords: Digital Economy, Macroeconomics, SEM-PLS, Stock Liquidity, Stock Price